Membrane proteins and squalene-hydrosqualene profile in methanoarchaeon Methanothermobacter thermautotrophicus resistant to N,N'-dicyclohexylcarbodiimide - Nováková, Zuzana; Šurín, Stanislav; Blaško, Jaroslav; Majerník, Alan; Šmigáň, Peter (Folia microbiologica, 2008)
The biochemical basis of a defective bioenergetic system was attempted to be determined in N,N'-dicyclohexylcarbodiimide (DCCD)-resistant mutant of Methanothermobacter thermautotrophicus. Components participating in the maintenance of methanoarchaeal membrane structure and function, such as the composition of the mixture of squalene and its hydrosqualene derivatives and also properties of membrane-associated proteins were compared in wild-type and mutant cells. The impairment of the bioenergetic system in DCCD-resistant mutant was detectable in the membrane-protein profile; it was also accompanied by changes in proportions of squalene-hydrosqualenes.
Keywords: antibiotická rezistence; Energy Metabolism; Mutation; skvalen; Membrane Proteins; Cell Membrane; Methanobacteriaceae; Drug Resistance, Microbial; mutace; Squalene; membránové proteiny; energetický metabolismus; buněčná membrána; Dicyclohexylcarbodiimide; dicyklohexylkarbodiimid